Ateliê pedagógico : construções de materiais didáticos na formação crítica de professores/as de língua inglesa - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
This research aimed to study the constructed meanings in a critical teacher education through a workshop experience of development teaching materials. Happening during the covid-19 pandemic, the workshop proposed the digital and collaborative construction of critical English language teaching materials. The study was developed in a Letters course – Portuguese/English, at the State University of Goiás – and had the participation of fourteen undergraduates, two collaborating professors and my participation. Through the workshop, three didactic courses of linguistic education were created, which pedagogically address mental health, gender inequality and food culture. For this study, I consider a qualitative-interpretative research orientation (DENZIN; LINCOLN, 2006). Here I use many sources of empirical material to study the meanings constructed by the participants, like an opening activity; the discourses shared in the formative moments; electronic message exchanges; an internship narrative; the didactic materials elaborated; and a post-workshop talk. Through the empirical material, it was possible to observe that the workshop experience made possible to destabilize the naturalized position of the didactic materials, proposing to the undergraduates to (re)think and create, in a local perspective, the didactic activities and technologies to be used in language education. Furthermore, the research for university and continuous teachers training that discuss the social, political and issues that involve teaching materials, as well its elaboration. Keywords: Critical teacher education. English language. Teaching materials. Language Education.
Ateliê pedagógico : creating teaching materials in the critical language teacher education
Keywords: Língua inglesa - Formação crítica de professores; Língua Inglesa - Materiais didáticos; Educação Linguística; English language - Critical teacher education; English language - Teaching materials; Language Education; CIENCIAS HUMANAS::EDUCACAO; LETRAS::LINGUAS ESTRANGEIRAS MODERNAS